Applicability of newly derived second and third molar maturity indices for indicating the legal age of 16 years in the Southern Chinese population. (September 2020) - Wang, Miaochen; Wang, Jian; Pan, Yuxia; Fan, Linfeng; Shen, Zhecheng; Ji, Fang; Tao, Jiang
Highlights: The cut-off values of 0.38 for I3M and 0.03 for I2M showed the best performance for discriminating adults from minors in Southern Chinese population, respectively. Compared with a single predictor (I3M ) alone, combining I3M and I2M can be more reliable for determining whether an individual is aged more than 16 years. Abstract: In China, forensic age estimation in the living has become increasingly important in these few years. Due to increasing juvenile crimes, the age of 16 years has become the legal age threshold for determining whether the juvenile criminal law or adult criminal law applies to the citizen. This study aimed to assess new cut-off values of the third molar maturity index (I3M ) and second molar maturity index (I2M ) at the legal age threshold of 16 years in Southern Chinese population and then to compare the applicability of the cut-off values of I3M and I2M we set for discriminating whether a subject is ≥ 16 years. Orthopantomograms (OPGs) of 671 healthy Southern Chinese subjects (332 males and 339 females), aged between 10 and 20 years, were studied. Logistic regression analysis was performed with chronological age (below 16 years and over 16 years) as a dichotomous dependent variable and, I3M, I2M, and sex as predictive variables. The high p -value for sex ( p = 0.861) reveals that this factor was not statistically significant in assessing the legal age of 16. The cut-off values of I3M < 0.38 and I2M < 0.03 were identified and used to distinguish between individuals who were or were not aged ≥ 16 years. Compared with a single predictor (I3M ) alone, combining I3M and I2M can be more reliable for determining whether an individual is aged more than 16 years. We found that accuracy was 88.52% (95% confidence interval CI, 86.11–90.94%) and sensitivity and specificity were 77.96% (95% CI, 74.82–81.10%) and 97.28% (95% CI, 96.04–98.51%), respectively. The estimated Bayes post-test probability was 99.12% (95% CI, 98.41–99.83%). In conclusion, combining I3M and I2M may be useful in legal and forensic practices to determine the legal age of 16 years in Southern Chinese individuals.